Law as a vehicle for peace in South Africa - Venter, F. (Koers, 1986)
Is the law at all an aid towards the defusing of the complex and potentially explosive political situation in which the Republic finds itself today? Seeing that the state is a creation of the law, the answer to this question has to be affirmative, because the contentious institutions and structures of the state can only be applied through legal process.